Effect of Ultrasonic Treatment on the Solubility of Sodium Sulphate Using Response Surface Methodology - Li, Hui; Zeng, Guisheng; Tu, Xinman (Asian Journal of Chemistry, 2013)
The effect of ultrasonic treatment on the solubility of sodium sulphate was investigated in this study. The influence of several single-factor experiments including temperature, ultrasonic time, ultrasonic power and rotation rate on the solubility of sodium sulphate was carried out. Response surface methodology (RSM), based on a three level, three variable central composite design (BBD), was employed to obtain the best possible combination of temperature (X1), ultrasonic time (X2) and ultrasonic power (X3) for maximum solubility according to the results from single-factor experiment. The 3-D response surface plot and the contour plot was derived from the mathematical models. The results also showed that the best conditions to attain the maximum solubility are met when temperature was 35 ºC, time was 20 min, power was 140 w. Under this condition, the experimental yield was 52.6321 g, which was well matched with the predictive yield.